'Involve me and I'll understand': creative capacity building for participatory design with rural Cambodian farmers. Issue 2 (3rd April 2019) - Drain, Andrew; Shekar, Aruna; Grigg, Nigel
Abstract: Participatory design (PD) has proven successful in the design of technologies in Western markets and shows promise as a method for humanitarian technology development. However, there have been few studies of PD in developing markets. In general, these studies have noted several process challenges due to cultural, societal and geographical differences. These challenges are restricting the widespread use of PD approaches for, and with underserved communities, and in turn reducing the long-term impact each project could make. This article presents findings from the implementation of creative capacity building workshops in rural Cambodia. Findings include suggested refinements to the design process; the need for flexible delivery methods; and the development of guiding questions for understanding the participant and ensuring appropriate educational content. The workshops show promise as a methodology for enhancing designer–participant collaboration in PD.